Adsorption of Cu(ii) from solution by modified magnetic starch St/Fe3O4-g-p(AA-r-HEMA). (4th October 2021) - Hou, Chengmin; Ma, Hanxiao; Cao, Congjun; Ding, Xiaojian; Duan, Jingting
Abstract : Magnetic starch was prepared, and then AA and HEMA were grafted on its surface to obtain St/Fe3 O4 - g -p(AA- r -HEMA) for the adsorption of Cu(ii ). Abstract : The composite particles (St/Fe3 O4 ) of starch and Fe3 O4 were prepared by a co-precipitation method. Then AA and HEMA were grafted and cross-linked on St/Fe3 O4 by a one-step method to obtain St/Fe3 O4 - g -p(AA- r -HEMA). The effects of the adsorbent dosage, pH value, initial Cu(ii ) concentration, time and temperature on adsorption were studied. Experiments showed that St/Fe3 O4 - g -p(AA- r -HEMA) showed a good adsorption performance for Cu(ii ), with a unit adsorption capacity of 75.5 mg g −1 and a maximum removal rate of 95.0%. The adsorption process followed the Langmuir model and the pseudo-second-order kinetic model, was dominated by chemical adsorption, and belonged to single-layer adsorption. Renewable performance studies showed that after 8 adsorption cycles, 91.2% of the first adsorption effect was still retained.